The transfer of sin: the debate on imputation in the English Antinomian Controversy (1690-1700) in its international and interconfessional context - Brink, Gert van den (Studies in reformed theology, 2025)
"According to the apostle Paul, Christ was made sin. What does this mean: can sin be transferred? Was Christ punished? At the end of the 17th century, in the so-called Third Antinomian Controversy English and Dutch Reformed theologians discussed the concept of imputation in its interrelationship with forgiveness, punishment, and justice. This study helps you to understand their complex and fascinating theological and philosophical reflections. Because the same themes had already extensively been discussed during the century before against Socinianism, the antinomian controversy is placed in an interconfessional and international context, highlighting the significance of Socinians and Hugo Grotius